Development and characterization of a double-crested cormorant hepatic cell line, DCH22, for chemical screening - Sharin, Tasnia; Crump, Doug; O’Brien, Jason M. (Frontiers in Toxicology, 2025)
There are currently no available cell lines for the ecologically relevant colonial waterbird species, the double-crested cormorant (DCCO). DCCOs are high trophic level aquatic birds that are used for routine contaminant monitoring programs in the Laurentian Great Lakes and marine coasts of Canada. Developing a DCCO cell line for in vitro toxicological screening will ideally provide improved understanding of the effects of environmental chemicals given the large differences in sensitivity between laboratory and wild avian species. In this study, an immortalized DCCO hepatic cell line, DCH22, was established from the liver of a day 22 female embryo as a potential alternative to primary DCCO embryonic hepatocytes (DCEH) for chemical screening. DCH22 cells were cultured for over a year and have hepatocyte-like morphology. Exposure to 3,3′,4,4′,5-pentachlorobiphenyl (PCB-126), benzo-a-pyrene, ß-napthoflavone and phenacetin induced CYP1A activity and mRNA expression in DCH22 3D spheroids. Induction of CYP3A activity and mRNA expression was observed following exposure to hexabromocyclododecane (HBCD), tris(1,3-dichloroisopropyl)phosphate, carbamazepine, and metyrapone. The phase II metabolism gene, UGT1A1, was upregulated following HBCD exposure and DCH22 spheroids expressed vitellogenin protein after exposure to 17α-ethinylestradiol. Based on these data, the novel DCH22 cell line, cultured as 3D spheroids, has potential use as an alternative to DCEH for chemical screening and will permit the evaluation of avian species differences in sensitivity from an in vitro screening perspective.